2023
DOI: 10.1155/2023/8669796
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fuzzy-RBF-CNN Ensemble Model for Short-Term Load Forecasting

Abstract: Accurate load forecasting (LF) plays an important role in the operation and decision-making process of the power grid. Although the stochastic and nonlinear behavior of loads is highly dependent on consumer energy requirements, that demands a high level of accuracy in LF. In spite of several research studies being performed in this field, accurate load forecasting remains an important consideration. In this article, the design of a hybrid short-term load forecasting model (STLF) is proposed. This work combines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Various EV owners have diferent demands for EVs, and Roni et al [10] conducted a study on EV charging in several areas in Seattle and found that the charging time of EVs in diferent regions varies. Based on power grid data, Yadav et al [11] established an RBF-CNN-integrated model to predict short-term load and validated its results. Terefore, analyzing the behavior of EV owners is of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Various EV owners have diferent demands for EVs, and Roni et al [10] conducted a study on EV charging in several areas in Seattle and found that the charging time of EVs in diferent regions varies. Based on power grid data, Yadav et al [11] established an RBF-CNN-integrated model to predict short-term load and validated its results. Terefore, analyzing the behavior of EV owners is of critical importance.…”
Section: Introductionmentioning
confidence: 99%